C-type lectin receptor agonists elicit functional IL21-expressing Tfh cells and induce primary B cell responses in neonates - Vono, Maria; Mastelic-Gavillet, Beatris; Mohr, Elodie; Östensson, Malin; Persson, Josefine; Olafsdottir, Thorunn A.; Lemeille, Sylvain; Pejoski, David; Hartley, Oliver; Christensen, Dennis; Andersen, Peter; Didierlaurent, Arnaud M.; et al. (Frontiers in Immunology, 2023)
Introduction C-type lectin receptor (CLR) agonists emerged as superior inducers of primary B cell responses in early life compared with Toll-like receptor (TLR) agonists, while both types of adjuvants are potent in adults. Methods Here, we explored the mechanisms accounting for the differences in neonatal adjuvanticity between a CLR-based (CAF®01) and a TLR4-based (GLA-SE) adjuvant administered with influenza hemagglutinin (HA) in neonatal mice, by using transcriptomics and systems biology analyses. Results On day 7 after immunization, HA/CAF01 increased IL6 and IL21 levels in the draining lymph nodes, while HA/GLA-SE increased IL10. CAF01 induced mixed Th1/Th17 neonatal responses while T cell responses induced by GLA-SE had a more pronounced Th2-profile. Only CAF01 induced T follicular helper (Tfh) cells expressing high levels of IL21 similar to levels induced in adult mice, which is essential for germinal center (GC) formation. Accordingly, only CAF01- induced neonatal Tfh cells activated adoptively transferred hen egg lysozyme (HEL)-specific B cells to form HEL+ GC B cells in neonatal mice upon vaccination with HEL-OVA. Discussion Collectively, the data show that CLR-based adjuvants are promising neonatal and infant adjuvants due to their ability to harness Tfh responses in early life.